Prostate myths: What is the prostate awareness in the general male population in Turkey? - Kulaksızoğlu, Haluk (Turk J Urol, 2014)
OBJECTIVE: The aim of the study was to evaluate prostate awareness in the general male population and discover the common misinformation about prostate diseases (PDs). MATERIAL AND METHODS: A cross-sectional population sampling was performed in the general population for men between the ages of 18–70 with a survey conducted by medical students. The survey consisted of 15 questions addressing different aspects of PDs and common misinformation in the general population. All participants were stratified according to age, degree of education, occupation and whether the person himself or a close relative had visited a urologist for PDs. All questionnaires were anonymous, and patients were informed about the confidentiality of the results. RESULTS: A total of 1004 men between the ages of 18–70 were included in the study (mean age 38.0±12.9 years). Of those included, 20.2% were primary school graduates, 8.6% were secondary school graduates, 25.5% were high school graduates, 39.8% were university graduates, and 5.8% had a doctorate or higher education. Of all 1004 men, 31.5% had seen a urologist or attended an interview with a close relative for a PDs-related visit in a urologist’s office; 56.2% reported “prostate” as a disease and only 16.5% as an organ. In terms of beliefs, 50.2% believed that all men had a “prostate,” 5.4% said that sexual activity would cause PDs, 13% thought that sexual activity would prevent PD, 24.9% reported that a rectal exam would affect sexual activity, and 63.5% believed that urinating when squatting would prevent prostate hyperplasia. Prostate cancer transmission to sexual partners was marked as true by 5% of the men. As many as 41.3% of the participants believed that early prostate surgery for BPH would prevent prostate cancer, and 13% reported that sexual activity ceases with prostate surgery and that retrograde ejaculation or anejaculation is the end of sexual activity in men. CONCLUSION: The survey clearly showed that prostate awareness is still very unsatisfactory in the Turkish male population and that urologists need to better inform the general population. PD knowledge is still lacking throughout all education levels. This is a unique study showing a cross-sectional analysis of the Turkish community; however, the applicability of these results to other communities should be evaluated.